PENGARUH PEMBERIAN PAKAN KONSENTRAT HIJAU TERHADAP KONSUMSI DAN KECERNAAN BAHAN KERING, BAHAN ORGANIK DAN LEMAK KASAR PADA KAMBING PERANAKAN ETAWA (Penelitian Di Peternak Rakyat Dusun Prodo Desa Klampok Kecamatan Singosari, Kabupaten Malang - Mau, Charles; Marhaeniyanto, Eko; Darmawan, Hariyadi (Fakultas Pertanian, 2018)
This research was conducted with the aim to know the effect of green concentrate use with the proportion of 10 - 30% of different leaf powder to feed intake level, and digestibility of etawa goat. Implementation of research in Klampok Village Singosari Subdistrict and proksimat analysis done in laboratory of Nutrition dan Feed Animal, Brawijaya University. The research material consisted of 16 male goats etawa rich makers, average body weight of 26.68 ± 9.01 kg.The materials used are bran, milled corn, soybean meal, coconut meal, mineral and molasses of Gliricidia sepium leaf powder, Calliandra calothyrsus, Leucaena leucocephala, Artocarpus heterophillus. Use of green flour on green concentrate with different proportions ie P0 without leaf meal, P1 using 10% leaf powder, P2 using 20% leaf powder, P3 30% leaf powder.The experimental method, using Randomized Blok Design (RBD) consisted of 4 treatments and 4 replications. Treatment of concentrate feed with 18% crude protein content.The results showed an non significant (P> 0.05) on the consumption of dry matter, organic matter, and crude fat. However, the effect was significantly (P